2021
DOI: 10.3390/healthcare9050505
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Work Value Awareness on Self-Rated Physical Health of Rural-to-Urban Migrant Workers in China

Abstract: We used data based on the China Labor-Force Dynamics Survey 2016 to examine the relationship between the work value awareness and the physical health of rural-to-urban migrant workers. The work value awareness was characterized by five dimensions: awareness of the emotional value, social value, respect value, ability value and interest value. Physical health was measured by a self-rated health assessment. The results from an IV-ordered probit model show that the awareness of work value has a statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The CES-D is one of the most widely used scales for measuring depression and mental health (56,57). It has been verified as valid for the assessment of depression and mental health status in a Chinese context (58)(59)(60)(61)(62). The CES-D scale is scored from 20 to 80, and a higher score indicates a higher level of depression and worse mental health (54).…”
Section: Measures Explained Variablesmentioning
confidence: 99%
“…The CES-D is one of the most widely used scales for measuring depression and mental health (56,57). It has been verified as valid for the assessment of depression and mental health status in a Chinese context (58)(59)(60)(61)(62). The CES-D scale is scored from 20 to 80, and a higher score indicates a higher level of depression and worse mental health (54).…”
Section: Measures Explained Variablesmentioning
confidence: 99%
“…A stable residence helps to establish a firm and lasting bond of relations. It promotes the accumulation and growth of favorable factors such as trust and reciprocity in social interaction, an essential way for individuals to gain survival value [63][64][65]. But most of the young farmers live in the dormitory provided by the units, and the proportion of housing purchases for them is low.…”
Section: Urban Pushing Forcementioning
confidence: 99%
“…The ancient Greek philosopher Socrates suggested that "the unexamined life is not worth living" [1]. Similarly, it is important for workers to recognize the value of their work since work value perception has been found to strongly affect workers' outcomes, both at work and beyond [2][3][4][5][6][7]. Work value perception generally refers to workers' perception of the value category, such as economic value, emotional value, social value, respect value, ability value, and interest value, and these above values in regard to the work that they are engaged in [8][9][10].…”
Section: Introductionmentioning
confidence: 99%